2015
DOI: 10.1016/j.cmrp.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic impact of the recent outbreak of H1N1

Abstract: Available online xxxKeywords: H1N1 Economic Social Morbidity Expenditure a b s t r a c t Background & aim: : Recent outbreak of H1N1 influenza leads to increased morbidity and mortality. High infection rate and virulence created panic among masses and huge health care burden. Socio-economic impact of H1N1 influenza has been underestimated. We describe socio-economic impact of H1N1 by taking hospitalization expenditure model. Method: In a prospective observational study at tertiary care centre in Northern India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…Numerous studies have assessed the economic impacts of infectious diseases ( Blake et al, 2003 ; Chou et al, 2004 ; Jonung and Roeger, 2006 ; Smith et al, 2011 ; Evans, et al, 2014 ; Kumar, et al, 2015 ). Several studies have suggested that the COVID-19 pandemic would cause great damages to China’s macro economy and sectoral output in the short run.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have assessed the economic impacts of infectious diseases ( Blake et al, 2003 ; Chou et al, 2004 ; Jonung and Roeger, 2006 ; Smith et al, 2011 ; Evans, et al, 2014 ; Kumar, et al, 2015 ). Several studies have suggested that the COVID-19 pandemic would cause great damages to China’s macro economy and sectoral output in the short run.…”
Section: Introductionmentioning
confidence: 99%
“…The term “pandemic” refers to such aspects of viral diseases as explosiveness, transmissibility, and the infection severity (Morens et al, 2009). However, the effects of pandemics are not limited to their physical consequences (e.g., Bloom et al, 2005; Brooks et al, 2020; Kumar et al, 2015; Page et al, 2012; Qiu et al, 2020; Reardon, 2015; Wang et al, 2020). Therefore, there is a need for a new term that will address the multidimensional nature of viral pandemic victimization.…”
mentioning
confidence: 99%
“…Effects of the medical cost and percentage of sensible population are enhanced by each other. The close association between the H1N1 flu with socioeconomic conditions indicates the essential role of public health resources in the variation of flu incidence (Ponnambalam et al 2012, Kumar et al 2015, Mulinari et al 2018. Compared with previous studies, this study provides more details about geographically regional effects of explanatory variables of the flu incidence.…”
Section: Discussionmentioning
confidence: 90%